Communiquer par l’image : Trois essais de culture visuelle. - Sylvie Fabre (Communiquer)
This book review examines Andrea Semprini’s semiodiscursive exploration of three (culturally significant) visual phenomena characteristic of our time. In Communication par l’image, a work representative of a methodology developed over years of research, Semprini articulates his socio-semiotic approach to communication and a culturalist perspective. Through three analytical essays on diverse objects, the author shows us the “possible world” that each of these visual elements contributes to creating.